Ignorance : literature and agnoiology - Bennett, Andrew, 1960 December 2- (Manchester University Press, 2009)
This text offers a new theory of & new ways of thinking about literature, with insights into literary theory. It offers an important rethinking of Romanticism & its influence on literary studies, from the 19th century to the present. It includes new readings of a range of authors including Wordsworth, Dickens & Seamus Heaney.
Keywords: English literature -- 19th century -- History and criticism.; English literature -- 20th century -- History and criticism.; Ignorance (Theory of knowledge) in literature.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Littérature anglaise -- 20e siècle -- Histoire et critique.; Ignorance dans la littérature.; Literature: History & Criticism.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- General.; English literature; Ignorance (Theory of knowledge) in literature; 1800-1999; Criticism, interpretation, etc.; Anthologies.